ANALISIS PERPINDAHAN LATERAL STRUKTUR BETON BERTULANG PADA BANGUNAN BERTINGKAT BERATURAN DAN KETIDAK BERATURAN HORIZONTAL - Simamora, Jawarta; Wibowo, Leonardus Setia Budi; Purwanto, Didik; Ray, Norman (Universitas Dr. Soetomo, 2020)
The effect of earthquake forces on buildings will certainly be different if applied to regular and irregular buildings. The performance of structures produced in irregular buildings will be different from the performance of irregular building structures for the same load intensity. In the earthquake resistant structure planning regulations, SNI 1726-2012 concerning structural irregularities. Where in this regulation there are two types of structural irregularities namely horizontal structural irregularities and vertical structural irregularities which are then subdivided into several types of irregularity. The study was carried out to compare the results of building structure performance with horizontal irregularity compared to regular buildings as seen from displacement, drift ratio, base shear, performance level based on ATC-40, differences in reinforcement weight. This research resulted in the largest displacement for the x-direction, namely the type A irregular building where it experiences a deviation of 0,49 m difference and for the y-direction of 0,44 m in the type A irregular building Type A. The biggest drift ratio of the x-direction and direction y is a Type B irregular building that is equal to 0,64 m for the x-direction and 0.57 m for the y-direction. The largest base shear occurs in regular buildings with Type B irregular buildings at 16.34%. the level of performance based on ATC-40 for all building models is immidiate occupancy, the biggest reinforcement need is the irregular building model B with a percentage difference of 11,20%.